Autoimmune Anti-Hu Antibody Limbic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the French Reference Center on Paraneoplastic Neurological Syndrome (PNS), Lyon Neuroscience Research Center, and other centers in France performed a retrospective study of children and adolescents with anti-Hu antibodies (Hu-Abs) collected by the Reference Center between Jan 1, 2000 and Dec 31, 2011.